Suspended Push-up Training Augments Size of not only Upper Limb but also Abdominal Muscles - Kohiruimaki, Ren; Maeo, Sumiaki; Kanehisa, Hiroaki (International Journal of Sports Medicine, 2019)
We investigated the effects of sling-based, suspended push-up training on muscle size and function of upper limb and abdominal muscles. Eight men conducted suspended push-ups to failure 3 sets/session, 3 sessions/week, for 8 weeks. The maximum number of push-ups during training gradually and significantly increased from the first to last training session (+92%), suggesting improved muscle endurance. After the training, muscle thickness of the elbow extensors (+16%) and flexors (+3%), as well as abdominal muscles (rectus abdominis: RA,+27%; external oblique: EO,+14%) significantly increased. No changes occurred in maximum isometric strength of elbow extension or flexion, nor in 1-repetition maximum bench press. In a follow-up experiment, electromyograms (EMGs) of RA, EO and internal oblique (IO) during suspended push-ups to failure were measured and normalized to those during maximum voluntary contraction of each muscle (% EMGmvc) in six men. EMG significantly increased when reaching failure in all muscles (RA: 46–88%, EO: 32–50%, IO: 19–52%, start-end), and was particularly high in RA. These results suggest that suspended push-up training can augment size of not only upper limb but also abdominal muscles, likely attributable to high muscle activities during exercise; however, this does not necessarily improve maximum strength after training thus warrants careful interpretation/application.
Keywords: muscle thickness; isometric strength; one-repetition maximum; training to failure; electromyography